2020
DOI: 10.1007/s12325-020-01417-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Issues in the Management of Cardiovascular Risk Factors in Diabetes During the COVID-19 Pandemic: A Review of Current Literature

Abstract: The COVID-19 outbreak was declared a pandemic on March 2020. Many patients with SARS-CoV-2 infection have underlying chronic medical conditions such as diabetes, cardiovascular disease (CVD), and hypertension. Patient-related outcomes are worse if there are associated comorbidities. We do not have enough evidence regarding the most appropriate management of patients with diabetes during COVID-19 infection. Insulin resistance and CVD together increase the inflammatory state of the body, which can contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…The available data do show no increased or even lower maternal mortality rate after infection [25], but it does not mean that pregnancy is a protective factor for severe infection. It was reported that severe infection mostly occurred in the elderly (> 60 years old), patients with basic diseases, such as diabetes, obesity, hypertension, coronary heart disease, cerebrovascular diseases, and other chronic diseases [26][27][28][29][30], as well as those who did not receive timely treatment or delay treatment [31]. Pregnant women are usually younger without primary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The available data do show no increased or even lower maternal mortality rate after infection [25], but it does not mean that pregnancy is a protective factor for severe infection. It was reported that severe infection mostly occurred in the elderly (> 60 years old), patients with basic diseases, such as diabetes, obesity, hypertension, coronary heart disease, cerebrovascular diseases, and other chronic diseases [26][27][28][29][30], as well as those who did not receive timely treatment or delay treatment [31]. Pregnant women are usually younger without primary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…150,151 GLP-1 receptor agonists can also potentially decrease inflammatory response in patients with COVID-19 by activation of AMPK and blockade of NF-KB. 152,153 ACE inhibitors and ARBs have also been reported to increase ACE2 expression, 37,38 and it was suggested that perhaps their use should be discontinued in patients with diabetes and the medications be changed to other agents, if possible. However, detailed reports have not shown any negative effects of these agents in patients with diabetes who acquire COVID-19.…”
Section: Medical Management Of Diabetes and Covid-19mentioning
confidence: 99%
“…GLP‐1 receptor agonists can also potentially decrease inflammatory response in patients with COVID‐19 by activation of AMPK and blockade of NF‐KB 152,153 …”
Section: Medical Management Of Diabetes and Covid‐19mentioning
confidence: 99%
“…According to the last reports, 20%–50% of patients with progressive disease reported with comorbid diseases including diabetes, hypertension, other cardiovascular system diseases, immunological disease, asthma, and chronic obstructive pulmonary disease (COPD) 11 . Other studies indicated a high mortality rate in patients with more than one comorbidity status; moreover, ARDS developed more than threefold in a patient without comorbidity 12–15 …”
Section: Introductionmentioning
confidence: 99%
“…11 Other studies indicated a high mortality rate in patients with more than one comorbidity status; moreover, ARDS developed more than threefold in a patient without comorbidity. [12][13][14][15] Our objective was to compare the serious adverse risk of smoking versus diabetes comorbidities and outcomes of patients with COVID-19.…”
mentioning
confidence: 99%